The Future University in the Eyes of Today’s Students - Abdrasheva, Dana; Morales, Diana; Sabzalieva, Emma (International Higher Education, 2022)
What do today’s students think about the university of the future? What are their hopes and fears, when thinking ahead to 2050? Based on focus groups consultations conducted as part of UNESCO’s Futures of Education initiative, key issues include the transformation of campus experiences by technology; a paradigm shift from mobility to engagement; cocreated learning environments; climate change concerns; links between higher education and the labor market; and the impact of artificial intelligence on employment.